Analysis of Total Anthocyanin Content on Ethanol Extract of Purple Sweet Potato (Ipomoea batatas L.) and Purple Yam (Dioscoreaalata L.) with Differential pH Method - Yuri Pratiwi Utami , Abdul Halim Umar, Ernawati (Jurnal Farmasi dan Ilmu Pengobatan, 2016)
Food processing industry, which is developing rapidly, leads to increase the use of dyes, especially natural dyes. One of the natural dyes found in plants is anthocyanin. In this research, the researcher analyzed the anthocyanin content in purple sweet potato (Ipomoea batatas L.) and purple yam (DioscoreaalataL.). Purple sweet potato and purple yam were extracted with 70% ethanol acidified with HCl 1%. The analysis was conducted using differential pH with absorbance measured in the UV-Vis spectrophotometer on 510 nm and 700 nm wavelength. The results showed that total anthocyanin content in purple sweet potato was 5.0 mg/L and in purple yam was 1.6 mg/L.